Effectiveness of Iontophoresis Treatment on Knee Osteoarthritis - Özlem Altındağ; Neslihan Soran; Metin Erçin; Leman Ege (Archives of Rheumatology, 2009)
Objective: Osteoarthritis is the most common joint disease causing disability. The primary goals for osteoarthritis therapy are to relieve pain, maintain or improve functional status, and minimize deformity. Many treatment options, including non-pharmacological and pharmacological measures, have been recommended in the management of osteoarthritis. Among the non-pharmacological approaches is physiotherapy, which involves the use of physical modalities like heat therapy, exercise therapy, electrical stimulation, therapeutic ultrasound, iontophoresis, and phonophoresis. The aim of our study was to retrospectively evaluate the efficacy of iontophoresis in patients with knee osteoarthritis. Materials and Methods: The study group included 40 patients with knee osteoarthritis to whom ketoprofen gel iontophoresis was applied. Pre-treatment and post-treatment pain, functional status and physical limitation were evaluated by Visual Analogue Scale (VAS), Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) and Lequesne Index, respectively. Results: There was significant difference between the pre- and post-treatment evaluation in all parameters (p<0.05). Conclusion: Iontophoresis may be considered as an alternative therapy in knee osteoarthritis that is inexpensive, simple and non-invasive. (Turk J Rheumatol 2009; 24: 136-9)